Genetics Behind the Glycosylation Patterns in the Biosynthesis of Dalbaheptides - Yushchuk, Oleksandr; Zhukrovska, Kseniia; Berini, Francesca; Fedorenko, Victor; Marinelli, Flavia (Frontiers in Chemistry, 2022)
Glycopeptide antibiotics are valuable natural metabolites endowed with different pharmacological properties. Among them are dalbaheptides, used to treat different infections caused by multidrug-resistant Gram-positive pathogens. Dalbaheptides are produced by soil-dwelling high G-C Gram-positive actinobacteria. Their biosynthetic pathways are encoded within large biosynthetic gene clusters. A non-ribosomally synthesized heptapeptide aglycone is the common scaffold for all dalbaheptides. Different enzymatic tailoring steps, including glycosylation, are further involved in decorating it. Glycosylation of dalbaheptides is crucial conferring them specific biological activities. It is achieved by a plethora of glycosyltransferases, encoded within the corresponding biosynthetic gene clusters, able to install different sugar residues. These sugars might originate from primary metabolism, or, alternatively, their biosynthesis might be encoded within the biosynthetic gene clusters. Already installed monosaccharides might be further enzymatically modified or work as substrates for additional glycosylation. In the current minireview, we cover recent updates concerning the genetics and enzymology behind the glycosylation of dalbaheptides, building a detailed and consecutive picture of this process and of its biological evolution. A thorough understanding of how glycosyltransferases function in dalbaheptide biosynthesis might open new ways to use them in chemo-enzymes synthesis and/or in combinatorial biosynthesis for building novel glycosylated antibiotics.